Mesozoic intraplate granitic magmatism in the Altai accretionary orogen, NW China: implications for the orogenic architecture and crustal growth - Wang, T.; Jahn, B.; Kovach, V.P.; Tong, Y.; Wilde, Simon; Hong, D.; Li, S.; Salnikova, E.B. (American Journal of Science, 2014)
The Central Asian Orogenic Belt (CAOB) is the world's largest Phanerozoic accretionary orogen and is the most important site for juvenile crustal growth in the Phanerozoic. In this work, we employed U-Pb zircon geochronology to identify the early and middle Mesozoic intraplate granitic intrusive events in the Chinese Altai segment of the southern CAOB in order to better understand the crustal architecture of the CAOB. We also used whole-rock geochemical, Sr-Nd isotopic and zircon Hf isotopic data to constrain the generation for these granitic rocks and to evaluate the implications for vertical crustal growth in this region. The Early Mesozoic granitic intrusions were emplaced between 220 and 200 Ma in the central Altai “microcontinental terrane” (also widely referred to as Units 2 and 3). The granites have shoshonitic and high-K calc-alkaline affinities and show the characteristics of differentiated I-type granite. The whole-rock initial 87Sr/86Sr ratios (0.7058-0.7128) and εNd(210) values (−0.6 to −4.3), as well as the zircon εHf(t) values (−4.0 to +5.0) and two-stage Hf model ages (0.94-1.52 Ga), suggest that the granitic magmas were produced from a mixed source with both mantle-derived and recycled crustal components. The middle Mesozoic granites were emplaced at ~150 Ma in the southern Altai “accretionary terrane” (Units 4 and 5). They show A-type characteristics with the REE tetrad effect and have positive εNd(151) whole-rock values of +1.0 to +5.2 and two-stage Nd model ages (TDM2) of 0.6 to 1.0 Ga. Zircon Hf data show positive zircon εHf(151) values of +1 to +8 and two-stage Hf model ages of 0.6 to 1.2 Ga. The Nd-Hf isotopic data suggest that the granitic magmas were derived from short-lived juvenile mantle-derived materials. Thus, the isotopic signatures of all the Mesozoic granites from the central (old terrane) and southern (young accretional terrane) Altai suggest that the basement of both terranes has retained its original nature. The data further imply that the Altai orogen has kept its original architecture of Paleozoic horizontal accretion during Mesozoic time, as commonly observed in accretionary orogens where horizontal tectonics are dominant. All the early Mesozoic intrusions in the Altai were emplaced in an intraplate anorogenic setting; hence are distinguished from the contemporaneous syn- or post-orogenic magmatism in the eastern CAOB. We conclude that the early Mesozoic granites in the CAOB were emplaced in a variety of tectonic settings.